IMPROVING SOCIAL COMMUNITY ACTIVITIES IN DIGITAL MEDIA THROUGH CONTENT MANAGEMENT TRAINING AND STORYTELLING TECHNIQUES - Wenny Desty Febrian; Bias Yulisa Geni; Muhamad Al Faruq Abdullah (Universitas Sahid, 2025)
This community service activity aims to enhance the digital capacity of women-led social communities in Kranggan, Bekasi, through content management training and storytelling techniques. In the digital era, the ability to create and manage content is essential for maintaining visibility and increasing engagement in online spaces. Conducted on May 25, 2025, the program involved 30 female participants from local social organizations. The training focused on developing compelling content, impactful narratives, and utilizing platforms like Instagram and TikTok to support community initiatives. The results indicate improved participant understanding of digital content and storytelling concepts, as well as greater confidence in using social media positively and productively. This program contributes significantly to digital-based community empowerment and opens up creative opportunities for women to be actively involved in public discourse through online platforms.